APOA5 gene polymorphism assessment and association with hypertriglyceridemia in the military force of the State of Goiás (Research, Society and Development, 2021)
According to the World Health Organization (WHO), dyslipidemias are determinant for the onset of cardiovascular diseases and represent more than 30% of global deaths. Changes in serum lipid levels are a direct consequence of dyslipidemia.   This study aimed to verify the relationship between genetic polymorphism APOA5  and dyslipidemia. This is a case-control study with 199 officers of the military force of the state of Goiás in which the relationship between lipid profile and genetic polymorphism rs964184 was evaluated. Real-time Polymerase Chain Reaction (real-time PCR) was used to identify genetic polymorphism rs964184. Of the participants analyzed, 93% were male and 7% female, the lipid profile showed that 115 participants had dyslipidemia (group of cases) and 84 were within the reference range (control group). The genetic polymorphism rs964184 of the case group showed that 64.3% (74/115) of the participants had genotype CC, 33.0% (38/115) had cg genotype and 2.6% (3/115) had GG genotype. In the control group, 69.0% (58/84) had genotype CC, 27.4% (23/84) had cg genotype, 3.6% (3/84) had GG genotype. In conclusion, the G alllea is related to high levels of triglycerides (≥ 150 mg/dL) and the C allea is related to normal HDL cholesterol levels (≥ 40 mg/dL). Therefore, homozygous (GG) or heterozygous (CG) individuals are more inclined to have high triglycerides and low HDL cholesterol levels, which are associated with an increased risk of developing cardiovascular disease.